Prison news service - No. 52 ... - Unav (University of Victoria Libraries, 2020)
The Prison News Network (PNS) focuses on political trials, repressive abuses of imprisonment and the resistance to such oppression. It was joined with another existing prison periodical called Marionette made by prisoners for prisoners and the general public to spread awareness of the conditions prisons, Marion Penitentiary, Illinois in particular. PNS editor: Bulldozer Collective. Articles include: "Renewed attacks in Canada's ongoing war against the First Nations"; "Our task! our duty: to build"; "Sabo denies new trial"; "Inquiry at Prison for Women"; "Letter from P4W"; "Seeking redress for hundreds of women imprisoned under old law"; "In Pennsylvania life means life"; Dozer notes; "Getting high in jail: legal vs illegal drugs"; "Political prisoners and continued repression in Chile;" "Prisoners' Justice Day - 1995"; "P.O.W.s threatened with death in Indiana: Ziyron Yisrayah. Khalfani Khaldun"; "Direct action in Ohio: the people fight back"; "Perotti hungerstrike"; "The women's crusade for reparations and ...